HIPPIES CHARACTERISTICS IN PEACE, LOVE & MISUNDERSTANDING MOVIE - Niesrin, Niesrin (LANTERN (Journal on English Language, Culture and Literature), 2015)
More than half  a century, hippie counterculture has lived and grown in the United States. Hippie, a group of people that against the mainstream culture, has unique characteristics to distinguish itself with the mainstream culture. There are some characteristics of hippie; having long hair, wearing conspicuous colored clothes, adhering communal living, having free sex, being addicted to drugs, being in doubt about American materialism, commercialism, cultural and political institutions. To prove that the characteristics are visible on hippie followers or not,  the writer uses Peace, Love & Misunderstanding movie produced by Bruce Beresford as the object of research. This movie tells about the different views between non-hippie members and hippie members in Woodstock. The result of this thesis is that all hippie characteristics are still shown on hippie members in Woodstock.